THE DIFFERENCE BETWEEN ENGLISH ACCENTS AND DIALECTS - Abduvokhidova Shakhribonu Akmalovna (European Journal of Humanities and Educational Advancements, 2021)
The article sheds its light on the difference between English accents and dialects all over the world which are the most significant aspects of learning EFL as SL which are the proper English pronunciation so that the teachers of English can be qualified to teach English to the students, This article tries to clarify the history of accents and dialects, their kind their roles in language change.